Exploring Experience and First Impression in The Liminal Spaces (Case Studies: Corridors and Stairs in Campus Environment) - Naja, Muhammad Farhat; Kuswanto, Iqbal Raihan; Purnama, Alan; Fathurraziqin, Habib; Wardhani, Mustika Kusumaning (Journal of Architectural Design and Urbanism, 2023)
Humans and their feelings are a 'unique' study in architectural design, such as how humans behave in some spatial settings. Spatial settings are usually defined as an environment that contains specific activities. However, what about transitional spaces or corridors that only serve as intermediaries for 'some walking experience'? The discussion related to liminal space becomes interesting, mainly when studied from the perspective of architectural psychology. This study aims to investigate human experiences and perceptions of liminal spaces, focusing on two locations: the corridors and the stairs at the campus. The research method used is mixed methods, with random samplings collected through an online survey to explore feelings, visuals, and hearing responses to liminal spaces. The study results show that respondents who have experienced being in a liminal space tend to have contra-perceptions of the Alienation theory by Marx, which can be attributed to the habits of the respondents in dealing with that space and their objective nature. Meanwhile, respondents with perceptions that align with Alienation theory tend to be influenced by their feelings and visual imagination. Moreover, respondents whose perceptions aligned with the theory expressed their discomfort and anxiety caused by unconducive room conditions. This research contributes to understanding human experiences and perceptions in liminal spaces with limitations including a small number of respondents and intangible indicators, making it difficult to explain perceptions in nominal terms. Thus, this research can broaden the understanding of architectural psychology and spatial perception.